A review on thermal comfort in educational buildings of Southeast Asia Region / Nurul Azreen Azmi, Asniza Hamimi Abdul Tharim and Mohamad Zaki Yusof - Azmi, Nurul Azreen; Abdul Tharim, Asniza Hamimi; Yusof, Mohamad Zaki (2021)
The thermal comfort in a classroom plays an important role in students’ life as it affects the comfort, health as well as the students’ learning performance. Students spend most of their time at school and in the classroom. Therefore, it is crucial that the thermal comfort in the classroom must be considered carefully because of the high occupant density and the negative influences that unsatisfactorily thermal environments may have on learning and students’ performance. This paper presents an overview of thermal comfort studies in educational buildings over the last twenty years that were carried out in countries within the South East Asia region. These countries have the same tropical climates which are generally warm all year round. The study is divided into two sections; the first section reviews the variables which are measured to determine thermal comfort and the second reviewing study results based on the educational stage, and the applied thermal comfort approach. Discussion on variables and parameters will help to outline the priorities for the future research agenda in this field. Thus, this study will provide robust evidence that there is a need for thermal comfort studies for students with different ages and different stages of their education.